Lower function, quality of life, and survival rate after total knee arthroplasty for posttraumatic arthritis than for primary arthritis. (2014) - Lunebourg, Alexandre; Parratte, Sebastien; Gay, André; Ollivier, Matthieu; Garcia-Parra, Kleber; Argenson, Jean-Noël
Abstract : Background and purpose — Total knee arthroplasty (TKA) for treatment of end-stage posttraumatic arthritis (PTA) has specific technical difficulties and complications. We compared clinical outcome, postoperative quality of life (QOL), and survivorship after TKA done for PTA with those after TKA performed for primary arthritis (PA). Patients and methods — We retrospectively reviewed patients who were operated on at our institution for PTA between 1998 and 2005 (33 knees), and compared them to a matched group of patients who were operated on for PA during the same period (407 knees). Clinical outcomes and postoperative QOL were compared in the 2 groups using Knee Society score (KSS), range of motion (ROM) of the knee, and the knee osteoarthritis outcomes score (KOOS). Implant survival rate was calculated using Kaplan-Meier analysis. Results — At a mean follow-up of 11 (5–15) years, KSS knee increased from mean 39 (SD 18) to 87 (SD 16) in the PA group (p = 0.003), and from 31 (SD 11) to 77 (SD 15) in the PTA group (p = 0.003). KSS function increased from 55 (12) to 89 (25) in the PA group (p = 0.008) and from 44 (SD 14) to 81 (SD 10) in the PTA group (p = 0.008). Postoperative ROM also improved in both groups, from 83° to 108° in the PTA group (p < 0.001) as opposed to 116° to 127° in the PA group (p = 0.001), with lower results in the PTA group (p < 0.001). KOOS was lower in the PTA group (p < 0.001). The survival rate of TKA at 10 years with an endpoint defined as "any surgery on the operated knee" showed better results in the PA group (99%, CI: 98–100 vs. 79%, CI: 69–89; p < 0.001). Interpretation — Patients and surgeons should be aware that clinical outcome and implant survival after TKA for PTA are lower than after TKA done for PA